Correction to: The Athena X-IFU Instrument Simulator xifusim (Journal of Low Temperature Physics, (2022), 10.1007/s10909-022-02700-4) - Kirsch, Christian; Lorenz, Maximilian; Peille, P.; Dauser, Thomas; Ceballos, M. T.; Cobo, B.; Merino-Alonso, P. E.; Cucchetti, E.; Smith, S. J.; Gottardi, L.; Den Hartog, R. H.; Miniussi, A.; et al. (Journal of Low Temperature Physics, 2022)
The original version of this article unfortunately contained a mistake. The co-author "R. H. den Hartog" affiliation should read as "SRON Netherlands Institute for Space Reseach, Niels Bohrweg 4, 2333 CA Leiden, Netherlands" instead of "Friedrich- Alexander-Universität Erlangen-Nürnberg, Dr. Karl Remeis-Observatory & ECAP, Sternwartstr. 7, Bamberg 96049, Germany". It is now corrected with this correction.
CRIS-Team Scopus Importer:2022-04-29